Chapter 3: Laplace Transform: FT Fs
Chapter 3: Laplace Transform: FT Fs
Chapter 3: Laplace Transform: FT Fs
3.1 Introduction
In reality, Laplace transform has many applications in science and engineering. It has important applications in
mathematics, mechanical vibrations, electrical circuits and control engineering. The main idea behind the
Laplace transformation is that we can solve an equation containing differential equation and integral terms by
transforming the equation in t-domain to one in s-domain with the intention that the problem easier to solve. In
mathematics, it is used for solving ordinary differential equation and integral equations. We begin our discussion
with the definition of Laplace transform.
{
Laplace Transform, f ( t ) = F ( s ) }
f (t ) F (s)
{
Inverse Laplace Transform, −1 F ( s ) = f ( t ) }
Definition 3.1
Given a function, f (t ), defined for all t ≥ 0. The Laplace transform of f (t ) is defined as
the following integral
∞
L{ f=
(t )} F=
(s) ∫ f (t )e − st dt
0
Since the integral in an improper integral, by definition evaluated according to the rule
∞ T
= {
f ( t )} e f ( t ) dt
∫=
− st
lim ∫ e − st f ( t ) dt
T →∞
0 0
Since the result of integral (3.1) depend on s , we can write:
∞ T
= {
f ( t )} e − st f ( t ) dt lim ∫=
∫= e − st f ( t ) dt F ( s )
T →∞
0 0
{ y ( t )} = Y ( s )
{ }
*Example 2: Using the definition of the Laplace transformation, determine f ( t ) if
2 0 ≤ t < 1
( t ) t 1 ≤ t < 4
f=
0 t≥4
Solution:
{ }
Example 3: Using the definition of the Laplace transformation, determine f ( t ) if
t 0≤t <2
f ( t ) = 4 − t 2 ≤ t < 4
0 t≥4
Solution:
(ii) Next, find the Laplace transform of the function obtained in (i) by using the definition of Laplace transform.
Table of Laplace transform are shown in Figure 1. These are generally used after analysing some elementary
function by using the definition.
f (t ) F ( s ) = L { f (t )} f (t ) F ( s ) = L { f (t )}
a a b
e at sin bt
(s − a) + b2
2
s
n! s−a
t n ,=
n 1, 2, … e at cos bt
s n +1 (s − a) + b2
2
1 n!
e at t n e at
(s − a)
n +1
s−a
a dn
sin at
s + a2
2
t n f (t ) (−1) n [ F ( s)]
ds n
cos at s F ( s − a)
e at f (t )
s + a2
2
s y′′(t )
cosh at s 2Y ( s ) − sy (0) − y′(0)
s − a2
2
Example 1: By using the table of Laplace transforms, find the Laplace transforms for given f ( t ) .
a) f (t ) = 5
Solution:
b) f ( t ) = e3t
Solution:
c) f ( t ) = cos 3t
Solution:
d) f (t ) = t 3
Solution:
2
e) f ( t ) = sinh t
3
Solution:
5
f) f ( t ) = cosh t
4
Solution:
g) f ( t ) = sin 4t
Solution:
h) f ( t ) = e −10t
Solution:
Properties of LT
Linearity
First Shift
Multiply by 𝑡𝑡 𝑛𝑛
L {α f (t ) + β g (t )} = α L { f (t )} + β L { g (t )} = α F ( s ) + β G ( s ) .
b) {
2t 4 − e −4t }
Solution:
c) {
−2 cos 5t + 6t − 9e −5t }
Solution:
L {e at f (=
t )} F ( s − a ) .
{
Proof: f ( t )} = e − st f ( t )
∫
0
∞
= ∫ e− ( s −a )t f ( t )
0
∞
= ∫e
− pt
f ( t ); p= s − a
0
= F ( p ) since p= s − a
= F (s − a)
Solution:
b) f ( t ) = e −4t sin ( 3t )
Solution:
c) (t )
f= ( sin t − cos t )
2
et
Solution:
dn
L {t n f (t )} = (−1) n [ F ( s)].
ds n
b) f ( t ) = t 2 sin t
Solution:
f ( t ) 5t cos t − 2t 2 sin t
c) =
Solution:
{ }
Laplace Transform, f ( t ) = F ( s )
f (t ) F (s)
{ }
Inverse Laplace Transform, −1 F ( s ) = f ( t )
{ }
If L f ( t ) = F ( s ) , then f ( t ) is called inverse Laplace transforms of F ( s ) and is written as
5
b) F (s) =
s − 36
2
Solution:
First Shift
Rational Function
Solution:
s+9
b) F (s) =
3s 2 + 12
Solution:
2 s + 5 3s − 9
F (s)
c) = +
s 2 + 25 s 2 + 4
Solution:
{ }
If L F ( s ) = f ( t ) and a is a constant, then
−1
L−1 { F ( s − a )} =
e at f ( t ) ,
L−1 { F ( s − a )} =
e at L−1 { F ( s )}.
1
a) F (s) =
4s − 3
Solution:
10
b) F (s) =
( s + 2)
4
Solution:
5s
c) F (s) =
( s − 2)
2
Solution:
−5
d) F (s) =
( s + 3) +9
2
Solution:
s+3
e) F (s) =
s + 6 s + 10
2
Solution:
1 2
F (s)
f) = +
2s + 1 s + 4
2
Solution:
12 s + 10 20 3 7
g) (s)
F= − 4 + 2 +
18s + 16 s
2
4s − 2 s − 3
Solution:
A
1. A linear factor ( s + a ) gives partial fraction .
(s + a)
A B
2. A repeated linear factor ( s + a ) gives partial fraction +
2
.
( s + a ) ( s + a )2
(s + a)
n
3. A repeated linear factor gives partial fraction
A B C Z
+ + + ... + .
(s + a) (s + a) (s + a)
2 3
(s + a)
n
As + B
4. A quadratic factor s 2 + bs + c gives .
s + bs + c
2
(s + bs + c )
n
5. A repeated quadratic factor gives
2
As + B Cs + D Ys + Z
+ + ... + .
( s + bs + c ) ( s 2 + bs + c )
2 2
( s 2
+ bs + c )
n
2s − 5
b) F (s) =
( s + 2s + 1) ( s − 1)
2
Solution:
2 s − 13
c) F (s) =
s ( s − 4 s + 13)
2
Solution:
s 2 + 2s − 4
d) F (s) = 3
s − 5s 2 + 2 s + 8
Solution:
The Laplace transform has many applications, mostly involving solving differential equations. Previously,
methods discussed in Chapter2 fail to apply if the equation involve f ( t ) in the form of piecewise continuous
functions, periodic functions, step function and delta function. By using this method, it provides us another way
for solving differential equations. In general, the steps in solving differential equations shown as follows
algorithm.
L { y ( t )} = Y ( s )
L { y=
′ ( t )} sY ( s ) − y ( 0 )
L { y′′ ( t )} = s 2Y ( s ) − sy ( 0 ) − y′ ( 0 )
L { y n (=
t )} s nY ( s ) − s n −1 y ( 0 ) − s n − 2 y′ ( 0 ) − − y n −1 ( 0 )
Method of Solution:
{
4. Apply inverse Laplace transform, −1 Y ( s ) }
5. Obtained y ( t ) which is original solution for given differential equation.
*Example 2: Use the method of Laplace transform to find the solution of the initial value problem
y '− 5 y =
15t , y ( 0) = 2
Solution:
Example 3: Use the method of Laplace transform to find the solution of the initial value problem
t 2 e3t , y ( 0 ) = −1
y′ − y =
Solution:
Solution:
*Example 2: Use the method of Laplace transform to find the solution of the initial value problem
y ( 0 ) 0,=
4e −2t , =
y′′ − y′ − 12 y = y ' ( 0) 1
Solution:
Example 3: Use the method of Laplace transform to find the solution of the initial value problem
y′′ + 6 y′ + 3 y =
0, = y ( 0 ) 1,=y ' ( 0) 4
Solution: